2000
DOI: 10.1007/bf02386755
|View full text |Cite
|
Sign up to set email alerts
|

Women living with HIV: Disclosure, violence, and social support

Abstract: This paper describes the frequency of women's disclosure of their HIV status, examines the extent to which they experience adverse social and physical consequences when others learn they are infected, and analyzes correlates of these negative outcomes. There were 257 HIV-positive women between the ages of 18 and 44, recruited from HIV/AIDS primary care clinics and from community sites, who completed a faceto-face interview. Women in the sample were 33 years old on average; 92% were AfricanAmerican; 54% had les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 9 publications
6
72
0
Order By: Relevance
“…In a study in Kenya, women who had ever used condoms had also experienced more partner violence [28]. Intimate partner violence has also been reported following disclosure of HIV results by women to their partners [30,[47][48][49]. Though we did not inquire into reasons for refusal of sex, it is likely that this could have been related to women's perceptions of their male partners' risk of HIV resulting in violence [14].…”
Section: Resultsmentioning
confidence: 99%
“…In a study in Kenya, women who had ever used condoms had also experienced more partner violence [28]. Intimate partner violence has also been reported following disclosure of HIV results by women to their partners [30,[47][48][49]. Though we did not inquire into reasons for refusal of sex, it is likely that this could have been related to women's perceptions of their male partners' risk of HIV resulting in violence [14].…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have shown that women with HIV are at increased risk for violence and that fear of such violence at the hands of sexual partners may inhibit disclosure (Gielen et al, 1997;Gielen, O'Campo, Faden, & Eke, 2000). It is possible that those in violent partnerships are less likely to disclose out of fear of retaliation, but others who disclose to previously non-violent partners become victims as a result.…”
Section: Discussionmentioning
confidence: 99%
“…However, disclosure of HIV status has also been associated with increases in adverse social outcomes, including violence, abandonment and divorce [13,14]. Male partner involvement in VCT may increase the likelihood of VCT uptake, behavior change, as well as improve compliance with pMTCT measures such as nevirapine (NVP) uptake.…”
Section: Introductionmentioning
confidence: 99%